PENGARUH MEDIA INFOGRAFIS TERHADAP PENGETAHUAN REMAJA PUTRI TENTANG MAKAN GIZI SEIMBANG (Politeknik Kesehatan Kemenkes Bandung, 2023)
Background: One of the risk factors for maternal mortality is mothers with Chronic Energy Deficiency (CED). Data from West Java Province basic health research (2018), the prevalence of CED in pregnant women in West Java is 14.08% and in Kuningan District is 18.36%, still above the average case in West Java. The highest prevalence of CED in West Java is in the group of adolescents aged 15-19 years. It is necessary to have early prevention by increasing the knowledge of young women about eating balanced nutrition through infographic media. Purpose: To know the influence of infographic media on the knowledge of young women about eating balanced nutrition in class XI MAN 1 Kuningan. Methods: This type of research is quantitative, using a quasi-experimental design with a one group pretest posttest design. Sampling using proportional random sampling technique, totaling 58 samples from 135 population of young women in class XI MAN 1 Kuningan. The research instrument to collect data was using a closed questionnaire and data analysis using the wilcoxon test. Results: The mean of pretest was 59.36 and posttest was 87.43. There was a significant increase of 28.07. There is an influence of infographic media on knowledge with p-value is 0.000 < 0.05. Conclusion: There is an influence of infographic media on the knowledge of young women eating balanced nutrition in Class XI MAN 1 Kuningan.